1999
DOI: 10.1093/ije/28.3.456
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and causes of death among Danish medical doctors 1973-1992

Abstract: Compared with the general population the doctors' mortality was low, but the mortality from external causes was increased, mainly due to an excess number of suicides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
49
3
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 10 publications
12
49
3
1
Order By: Relevance
“…Thus, results showed a consistent increase of suicide mortality with a standardized mortality ratio around 1.65, mainly due to the excessive number of suicides by poisoning [30]. Suicide verdicts had been provided by 87% of the remaining 223 physicians and open verdicts by 13% of them [31].…”
Section: Epidemiologymentioning
confidence: 75%
See 2 more Smart Citations
“…Thus, results showed a consistent increase of suicide mortality with a standardized mortality ratio around 1.65, mainly due to the excessive number of suicides by poisoning [30]. Suicide verdicts had been provided by 87% of the remaining 223 physicians and open verdicts by 13% of them [31].…”
Section: Epidemiologymentioning
confidence: 75%
“…An increase of suicide frequency by poisoning was a common characteristic seen in all subgroups, especially among male members of the Association of Specialist Physicians (AMS, acronym in Portuguese) and of the Organization of Practicing Physicians (OGP). Physicians presented an increase in the number of accidents and suicides by poisoning, as well as by other methods [30]. However, Siu, Yuen and Cheung, 2012, after analyzing 226 questionnaires applied to physicians enrolled in the Hong Kong Public Doctors' Association, observed that higher levels of physical and emotional burnout were associated with early age, less working experience, need of job shift changes, less children, and lower physical workout [28].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of several cancers (lung cancer in particular) among physicians is below that of the rest of the population (16)(17)(18). The difference partly remains even in comparison with other occupations in the highest social class.…”
Section: Discussionmentioning
confidence: 95%
“…Além disto, estão colocadas no mesmo grupo da Classificação Brasileira de Ocupações (CBO) do Ministério do Trabalho e Emprego 10 . Portanto, são ocupações adequadas para comparação, pois, além de apresentarem alto nível educacional, desfrutam de relativa estabilidade profissional 11 .…”
Section: Introductionunclassified